Social and Personal Significance of Evening Schools - Bozhilova, Vanya; Markova, Anna (Педагогически форум, 2025)
The article presents key aspects of evening schools in Bulgaria, which outline their specificity as institutions for free and systematic education of adults, offering general education, specialized, and vocational training to provide adults with better opportunities for labor market realization and career development. Special attention is paid to their importance for socially vulnerable groups in society and the possibilities for equal access, adaptation, and integration. The social and personal significance of evening schools is analyzed through a theoretical overview and in the context of an empirical study conducted during the period 2022 – 2024 among three of the four evening schools in the country. Through the study, the role of evening schools in meeting essential needs and forming values leads to conclusions about their key role in motivation for learning among adults and the formation of a sense of meaning, direction, and purpose, increasing the feeling of self-efficacy. The article concludes with a brief reflection made by the director of the 5th Vocational School "Penyo Penlev" in Sofia concerning his participation in a roundtable discussion dedicated to policies and practices for adult education in our country, specifically focusing on the mission of evening schools.